Sistem Informasi Akuntansi Pemesanan dan Pembayaran (Ordering and Billing) Makanan dan Minuman Berbasis Android Pada RM. Ayam Goreng â€œPadamaraâ€ Purbalingga - Marifati, Imam Soleh; Maarif, Vadlya (Universitas Bina Sarana Informatika, 2018)
Abstract - Ordering and billing transactions of food and beverages in a restaurant business are in the revenue cycle. Transactions in the revenue cycle have an important role for the company because from this transaction the company gets cash income. The use of information technology to support the transaction process can increase the effectiveness of the transaction process. Transactions can be processed quickly and accurately. Restaurant business can use accounting information systems to improve the effectiveness and efficiency of transaction processes in the revenue cycle. A computer-based accounting information system is needed in processing transactions. In this study, the authors developed the application of accounting information systems to process transactions in the revenue cycle for restaurant business activities. This application processes transaction data starting from ordering, payment and making revenue reports from restaurant business activities. Keywords: Order, Billing, Accounting Information System